Use of Titanium Dioxide Nanoparticles Biosynthesized by Bacillus Mycoides in Quantum Dot Sensitized Solar Cells - Monras-Charles, J (BioMed Central Ltd., 2014)
Background: One of the major challenges of nanotechnology during the last decade has been the development of new procedures to synthesize nanoparticles. In this context, biosynthetic methods have taken hold since they are simple, safe and eco-friendly. Results: In this study, we report the biosynthesis of TiO2 nanoparticles by an environmental isolate of Bacillus mycoides, a poorly described Gram-positive bacterium able to form colonies with novel morphologies. This isolate was able to produce TiO2 nanoparticles at 37°C in the presence of titanyl hydroxide. Biosynthesized nanoparticles have anatase polymorphic structure, spherical morphology, polydisperse size (40-60 nm) and an organic shell as determined by UV-vis spectroscopy, TEM, DLS and FTIR, respectively. Also, conversely to chemically produced nanoparticles, biosynthesized TiO2 do not display phototoxicity. In order to design less expensive and greener solar cells, biosynthesized nanoparticles were evaluated in Quantum Dot Sensitized Solar Cells (QDSSCs) and compared with chemically produced TiO2 nanoparticles. Solar cell parameters such as short circuit current density (I SC) and open circuit voltage (V OC) revealed that biosynthesized TiO2 nanoparticles can mobilize electrons in QDSSCs similarly than chemically produced TiO2. Conclusions: Our results indicate that bacterial extracellular production of TiO2 nanoparticles at low temperatures represents a novel alternative for the construction of green solar cells. © 2014 Órdenes-Aenishanslins et al.